2021
DOI: 10.1371/journal.pone.0257969
|View full text |Cite
|
Sign up to set email alerts
|

Does seniority always correlate with simulated intubation performance? Comparing endotracheal intubation performance across medical students, residents, and physicians using a high-fidelity simulator

Abstract: Background Endotracheal intubation is crucial in emergency medical care and anaesthesia. Our study employed a high-fidelity simulator to explore differences in intubation success rate and other skills between junior and senior physicians. Methods We examined the performance of 50 subjects, including undergraduate students (UGY), postgraduate trainees (PGY), residents (R), and attending physicians (VS). Each participant performed 12 intubations (i.e. 3 devices x 4 scenarios) on a high-fidelity simulator. Main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…Yau et al . [ 35 ] compared differences in intubation performance in success rate, time for intubation, force applied on incisor and tongue, and Cormac Lehane grades between medical students, residents, and junior and senior physicians on a high-fidelity simulator. They found that attending physicians were faster than medical students on intubation attempts.…”
Section: Discussionmentioning
confidence: 99%
“…Yau et al . [ 35 ] compared differences in intubation performance in success rate, time for intubation, force applied on incisor and tongue, and Cormac Lehane grades between medical students, residents, and junior and senior physicians on a high-fidelity simulator. They found that attending physicians were faster than medical students on intubation attempts.…”
Section: Discussionmentioning
confidence: 99%
“…Their age and clinical experience is therefore varied and, because proficiency greatly affects the outcome, it seems necessary to specify who the operator was in the 374 videolaryngoscopic intubations. If possible, the operators of tracheal intubation should be limited to clinicians with similar clinical experience [2,3]. Furthermore, the operator should be at least a senior resident skilled in tracheal intubation, in order to reduce bias.…”
mentioning
confidence: 99%